Sound change in Māori and the influence of New Zealand English. (28th March 2016) - Watson, Catherine I.; Maclagan, Margaret A.; King, Jeanette; Harlow, Ray; Keegan, Peter J.
Abstract : This article investigates sound change in the vowels of Māori, the indigenous language of New Zealand. It examines the relationship between sound changes in Māori and in New Zealand English, the more dominant language, with which Māori has been in close contact for nearly 200 years. We report on the analysis of three adult speaker groups whose birth dates span 100 years. All speakers were bilingual in Māori and New Zealand English. In total the speech of 31 men and 31 women was investigated. Analysis was done on the first and second formant values, extracted from the vowel targets. There has been considerable movement in the Māori vowel space. We find that the sound change in the Māori monophthongs can be directly attributed to the impact of New Zealand English, however the situation for the diphthongs is not so clear cut. There is some evidence that both New Zealand English monophthongs and diphthongs are impacting on the Māori diphthongs, but so too are the Māori monophthongs. We conclude that although New Zealand English has had a strong influence on Māori, there is very strong evidence that new generations of speakers of Māori are acquiring a phonemic system with its own internal parameters and consistencies.